2013
DOI: 10.1111/mmi.12226
|View full text |Cite
|
Sign up to set email alerts
|

Product feedback regulation implicated in translational control of the Trypanosoma brucei S‐adenosylmethionine decarboxylase regulatory subunit prozyme

Abstract: Summary Human African sleeping sickness (HAT) is caused by the parasitic protozoan Trypanosoma brucei. Polyamine biosynthesis is an important drug target in the treatment of HAT. Previously we showed that trypanosomatid S-adenosylmethionine decarboxylase (AdoMetDC), a key enzyme for biosynthesis of the polyamine spermidine, is activated by heterodimer formation with an inactive paralog termed prozyme. Furthermore, prozyme protein levels were regulated in response reduced AdoMetDC activity. Herein we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 74 publications
0
33
0
Order By: Relevance
“…However, quantitation of protein expression levels in the TbGS cDKO and RNAi lines suggests that Ͼ97% depletion of TbGS is required before trypanothione is depleted and cells begin to die, showing that a smallmolecule inhibitor of TbGS would need to nearly fully inhibit the enzyme. This is in contrast to ODC and AdoMetDC, where ϳ80% inhibition is sufficient (23,30).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, quantitation of protein expression levels in the TbGS cDKO and RNAi lines suggests that Ͼ97% depletion of TbGS is required before trypanothione is depleted and cells begin to die, showing that a smallmolecule inhibitor of TbGS would need to nearly fully inhibit the enzyme. This is in contrast to ODC and AdoMetDC, where ϳ80% inhibition is sufficient (23,30).…”
Section: Discussionmentioning
confidence: 86%
“…Spermidine levels remain unchanged after depletion of TbGS, consistent with this result. In a previous study, we showed that decarboxylated AdoMet levels were inversely proportional to AdoMetDC prozyme levels, suggesting that elevated decarboxylated AdoMet levels lead to reduced prozyme expression (30). SpdSyn from human and Plasmodium has been shown to be feedback inhibited by methylthioadenosine, a reaction product of SpdSyn chemistry (51,52), and both spermidine and methylthioadenosine have been demonstrated by crystallographic studies to bind SpdSyn (53).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations